Virome-wide ubiquitin ligase discovery reveals diverse mechanisms of immune evasion - Caleb R. Glassman; Kheewoong Baek; Gaopeng Hou; Qiru Zeng; Christopher Nardone; Kate B. Juergens; Eric Fujimura; Colin N. O’Leary; Mamie Z. Li; Joao A. Paulo; Eric S. Fischer; Siyuan Ding; et al. (Science, 2026)
Viruses are intracellular parasites that reprogram the host proteome to promote replication and evade immune recognition. We applied a virome-wide library of ~10,000 open reading frames to discover viral ubiquitin ligases, mapping their mechanisms of degradation and host substrates using targeted CRISPR screens and proteomics. These viral effectors could be classified as canonical ligases that mimic host E3s, hijackers that redirect host E3s, and non-canonical ligases that rewire Cullin-RING ligase machinery. These diverse strategies of virus-mediated degradation converged on immune-related substrates, including JAK1 and CUL1 β−TrCP , underscoring immune evasion as a major driver of viral ubiquitin ligase evolution. Our findings elucidate viral strategies for exploiting the ubiquitin–proteasome system with potential for therapeutic targeting.